The Role of Sekaten Tradition in Learning Physics to Conserve Culture in Yogyakarta - Novika Lestari (International Journal of Education and Literature, 2022)
Yogyakarta is one of the provinces in indonesia that has many culture, among them is sekaten tradition. Sekaten is a culture to commemorate the birth of prophet Muhammad SAW by Kesultanan Ngayogyakarta Hadiningrat. The activities include playing gamelan in Masjid Gede from 5 to 12 Rabiul Awal and closing by grebeg, parade of gunungan to be shared to society. Implementation sekaten in physics learning is a challenge for physics teacher in globalization era. This article aims to integrate physics curriculum in Indonesia and sekaten tradition. This reseach used qualitative method. The impacts are physics teachers can improve skill to manage learning from local culture. Hence, this article discuss method to analysis competence from physics curriculum in Indonesia which integrated sekaten tradition. This result is expected to be guidelines physics teachers to teached physics based sekaten tradition. Futhermore, it can improve student knowledge and attention about local culture